PENGARUH PENERAPAN METODE AMTSILATI TERHADAP PRESTASI BELAJAR SISWA PENERIMA BEASISWA MADRASAH ALIYAH I’DADIYYAH JOMBANG - Muhasim; Abdul Rouf; Dian Triana (FAI- Undar, 2021)
Education is a necessity in the light of religion and the State. But in practice many can not achieve the goal due to economic limitations. So the demand for mauun State educational institutions providing scholarships. Learning Arabic as the language of the Quran and the hadith is imperative for those who want to explore the science of religion. To accelerate the understanding of the Arabic language read the book then appear the various methods one of which is the method amtsilati. From the above researchers wanted to examine how the influence amtsilati methods on student achievement scholarship recipients integrated MA Al-Bahrul Ulum Jombang I'dadiyyahThis study uses a quantitative approach with two approaches expost factodan the data analysis using linear regression and Independent T test simple test.The results showed that of the 79 students were selected as sample was concluded that. There is no difference between student achievement receiving scholarships are not unified and integrated scholarship.Based on the above results it should. 1. Institutions MA Al-I'dadiyyah provide evaluation and monitoring of the administration beasisw. 2. Continuing program amtislati method because of the results of the research have a significant effect on student achievement both grantee recipients mauun not integrated.